Post-Holocaust France and the Jews, 1945-1955 - Hand, Seán; Katz, Steven T., 1944- (Elie Wiesel Center for Judaic Studies series., 2015)
Despite an outpouring of scholarship on the Holocaust, little work has focused on what happened to Europe's Jewish communities after the war ended. And unlike many other European nations in which the majority of the Jewish population perished, France had a significant post-war Jewish community that numbered in the hundreds of thousands. Post-Holocaust France and the Jews, 1945-1955 offers new insight on key aspects of French Jewish life in the decades following the end of World War II. How Jews had been treated during the war continued to influence both Jewish and non-Jewish society in the p ...